Between-Habitat Variation of Benthic Cover, Reef Fish Assemblage and Feeding Pressure on the Benthos at the Only Atoll in South Atlantic: Rocas Atoll, NE Brazil - Longo, G. O.; Morais, R. A.; Martins, C. D. L.; Mendes, T. C.; Aued, A. W.; Cândido, D. V.; de Oliveira, J. C.; Nunes, L. T.; Fontoura, L.; Sissini, M. N.; Teschima, M. M.; Silva, M. B.; et al. (PLOS ONE, 2015)
The Southwestern Atlantic harbors unique and relatively understudied reef systems, including the only atoll in South Atlantic: Rocas atoll. Located 230 km off the NE Brazilian coast, Rocas is formed by coralline red algae and vermetid mollusks, and is potentially one of the most “pristine” areas in Southwestern Atlantic. We provide the first comprehensive and integrative description of the fish and benthic communities inhabiting different shallow reef habitats of Rocas. We studied two contrasting tide pool habitats: open pools, which communicate with the open ocean even during low tides, thus more exposed to wave action; and closed pools, which remain isolated during low tide and are comparatively less exposed. Reef fish assemblages, benthic cover, algal turfs and fish feeding pressure on the benthos remarkably varied between open and closed pools. The planktivore Thalassoma noronhanum was the most abundant fish species in both habitats. In terms of biomass, the lemon shark Negaprion brevirostris and the omnivore Melichtys niger were dominant in open pools, while herbivorous fishes (mainly Acanthurus spp.) prevailed in closed pools. Overall benthic cover was dominated by algal turfs, composed of articulated calcareous algae in open pools and non-calcified algae in closed pools. Feeding pressure was dominated by acanthurids and was 10-fold lower in open pools than in closed pools. Besides different wave exposure conditions, such pattern could also be related to the presence of sharks in open pools, prompting herbivorous fish to feed more in closed pools. This might indirectly affect the structure of reef fish assemblages and benthic communities. The macroalgae Digenea simplex, which is uncommon in closed pools and abundant in the reef flat, was highly preferred in herbivory assays, indicating that herbivory by fishes might be shaping this distribution pattern. The variations in benthic and reef fish communities, and feeding pressure on the benthos between open and closed pools suggest that the dynamics in open pools is mostly driven by physical factors and the tolerance of organisms to harsh conditions, while in closed pools direct and indirect effects of species interactions also play an important role. Understanding the mechanisms shaping biological communities and how they scale-up to ecosystem functioning is particularly important on isolated near-pristine systems where natural processes can still be studied under limited human impact.